Electromagnetic performances and main parameter sensitivity effect on unbalance magnetic flux in a new single‑phase FEFSM with segmental rotor - Omar, Mohd Fairoz; Sulaiman, Erwan; Ahmad, Md. Zarafi (Springer Singapore, 2019)
Three-phase field excitation flux switching motor (FEFSM) with salient rotor structure has been introduced with their advantages of rotor easy temperature elimination and controllable FEC magnetic flux. Yet, the salient rotor structure is found to lead a longer magnetic flux path between stator and rotor parts, producing a weak flux linkage along with low torque performances. Hence, a new structure of single-phase FEFSM using segmental rotor with non-overlap windings is proposed with advantages of shorter magnetic flux path, light weight and robust rotor structure. Analysis on fundamental magnetic flux characteristics, armature and FEC magnetic flux linkages, cogging torque, back-Emf, various torque capabilities, refinement of unbalance magnetic flux, and torque-power versus speed characteristics are conducted using 2D FEA through JMAG Designer version 15. The results show that magnetic flux amplitude ratio has been improved by 41.2% while the highest torque and power achieved are 1.45 Nm and 343.8 W, respectively